PENGARUH EFIKASI DIRI DAN REGULASI DIRI TERHADAP PRESTASI BELAJAR MAHASISWA PROGRAM STUDI PENDIDIKAN MATEMATIKA UNIVERSITAS TADULAKO - Nurul Afiyah; Anggraini Anggraini; Gandung Sugita; Mustamin Idris (Universitas Tadulako, 2025)
This study aims to analyze: (1) the effect of self-efficacy on student math learning achievement, (2) the effect of self-regulation on student math learning achievement, and (3) the effect of self-efficacy and self-regulation simultaneously on student math learning achievement. This research used ex-post facto method and was conducted at Tadulako University. The study population was all Mathematics Education students class of 2023 which amounted to 130 people. The sample of 98 students was selected through proportional random sampling technique. The instruments used include self-efficacy questionnaire, self-regulation questionnaire, and GPA data of the first and second semester in mathematics courses as indicators of learning achievement. Data analysis begins with classical assumption tests: normality, linearity, heteroscedasticity, and autocorrelation. Furthermore, hypothesis testing was carried out with simple and multiple linear regression analysis, F test, and coefficient of determination test. The results showed that all classical assumptions were met. The results of hypothesis testing show that self-efficacy has a significant effect on math learning achievement with a contribution of 15.5% with a p-value < 0.05 namely <0.001, self-regulation has a significant effect with a contribution of 13.1% with a p-value < 0.05 namely <0.001, and simultaneously both have a significant effect on learning achievement with a contribution of 16.7% with a p-value < 0.05 namely <0.000. Although this effect is significant, the effect is relatively small, which indicates that not only self-efficacy and self-regulation are factors that determine student learning achievement.